PENYUSUNAN DRAF PERATURAN DESA SEBAGAI UPAYA MENINGKATKAN PARTISIPASI ANAK REMAJA DALAM KEGIATAN MAGRIB MENGAJI DI DESA BATUKARAS - Neneng Nurmalasari; Devi Silvia Dewi; Siti Julaeha; Acep Ridwan Maulana; Dian Herdiana (LPPM ITB AAS Indonesia Surakarta, 2023)
Maghrib reciting the Koran is a habitual program activity for reading, writing, understanding and reciting the Koran which is carried out between Maghrib and Isha. However, participation of teenagers in these activities tends to be low. The development of village regulations arose as an effort to increase the participation of teenagers in Maghrib Koran activities in Batukaras village, and aims to understand the extent to which village regulations can be an effective instrument in stimulating the participation of teenagers in Maghrib Koran activities. This service method involves surveys, interviews and observations. This service also identifies factors that influence adolescent participation and provides policy recommendations to support increasing adolescent participation. The implications of the policies resulting from this research can help the Batukaras village community, similar communities in efforts to increase the Maghrib recitation of the Koran and maintain religious, social and cultural values in society. The result of this service is village regulations regarding evening Koran recitation activities Key words: evening Koran recitation, participation, teenagers, village regulations.